A Comparison of a New Ultrasound-Based Whole Blood Viscoelastic Test (SEER Sonorheometry) Versus Thromboelastography in Cardiac Surgery. (December 2016) - Reynolds, Penny S.; Middleton, Paul; McCarthy, Harry; Spiess, Bruce D.
Abstract : BACKGROUND: Viscoelastic thromboelastography tests such as TEG™ are now routine for assessing the coagulation status of cardiac surgery patients. We compared TEG™ with a new technology, sonic estimation of elasticity via resonance (SEER) sonorheometry, to compare measures of coagulation dynamics of whole blood and assess its potential for rapid, near-point-of-care monitoring of hemostasis during cardiac surgery. METHODS: Whole blood coagulation assessment of a prospective cohort of 50 cardiac surgery patients was performed using SEER sonorheometry and blood samples collected at 4 time points during cardiac surgery: baseline before anesthetic induction, during cardiopulmonary bypass on rewarming, 10 minutes after heparin reversal by protamine, and on patient transfer to the intensive care unit. Clot strength trajectories (G, measured by TEG™; and clot stiffness measured by SEER sonorheometry) and clot times were assessed by repeated-measures mixed models. Strength of association between the 2 methods (clot stiffness and clot times) was assessed using a modified Bland-Altman method for repeated measures; Deming (orthogonal) regression was used to quantify method concordance (constant and proportional bias). RESULTS: Clot strength/stiffness and clot time measures for both techniques showed similar tracking of trajectories. Strength of association between methods was acceptable (correlations, 0.8–0.9); however, Deming regression detected substantial deviation (bias) between techniques. SEER clot stiffness values averaged approximately 10 hPa higher than corresponding G at all time points. Reaction time (TEG™) was 1 to 2.5 minutes longer than corresponding clot times (SEER). Laboratory times (from sample drop-off to results) were substantially less for SEER sonorheometry (median time, 11–17 minutes) compared with nonautomated kaolin TEG™ (median time, 42 minutes). CONCLUSIONS: Currently, no viscoelastic hemostatic analyzer system can be considered the "gold standard"; therefore, differences observed between TEG™ and SEER are of importance only because they show that the methods are not perfectly substitutable. Measurements of clot stiffness determined by the 2 methods were correlated but not interchangeable. Reasons for discrepancies include the substantial difference in the physical methods of inducing coagulation activation in samples and the mathematical assumptions underlying calculations of G. Future studies will be required to evaluate SEER sonorheometry's abilities to identify bleeding diatheses (sensitivity/specificity) or to develop treatment algorithms based on the new tests. Abstract : Published ahead of print May 6, 2016.